Assessment of Knowledge, Attitude and Practice among Community Pharmacists on Non-Prescription Drugs in Tamil Nadu - S.G, Santhoshkumar.; S, Prabakaran.; S. U, Deepika.; T, Vishnu.; Mohanta, Guru Prasad (Indian Journal of Pharmacy Practice)
Background: Self-medication is a concept where people can get medication directly from the pharmacists for their basic illness. Pharmacists, being the last line of direct contact with the patients, are responsible for educating the patients regarding the effects of self-medication. This study focuses on assessing the knowledge, attitude and practice among community pharmacists regarding non-prescription drugs in Tamil Nadu. Materials and Methods: A descriptive cross-sectional study was done. In our study, 383 responses were collected during the survey, which was executed for a period of 6 months. All responses obtained were analyzed and assessed using SPSS software and Microsoft Excel. Results: Knowledge percentage regarding the community pharmacists were found to be lesser which in turn affected their attitude and practice of dispensing prescription drugs. Pharmacists were barely involved in counselling the patients regarding the medication dispensed. Conclusion: Community pharmacists had an overall knowledge percentage of 55.35%, their attitude towards dispensing of prescription and non-prescription drugs were found to be better (75.97%). Community pharmacists had a good overall practice regarding non-prescription drugs.
Keywords: Knowledge; Attitude; Practice; Pharmacists; Non-prescription; Drugs